Fully differential cross section for single ionization in energetic C6+-He collisions - Abdurakhmanov, Ilkhom; Bray, Igor; Fursa, Dmitry; Kadyrov, Alisher; Stelbovics, Andris (American Physical Society, 2012)
The quantum-mechanical convergent close-coupling approach has been used to calculate the fully differential cross section for the single ionization of helium by C6+ ions at 100 MeV/amu. This allows one to test the quality of approximations used in standard approaches to the problem, particularly in geometries that are out of the scattering plane, where there is a strong disagreement between calculations and measurements. The obtained results show that the fully quantum-mechanical treatment of the internuclear motion does not enable one to get any better agreement with experimental data. In addition, we have performed calculations for the precise geometry where experimental data were collected, i.e., in the plane perpendicular to the momentum-transfer direction. We conclude that this rotation also has a minor effect on the shape of the cross section.